Granular Thermodynamic Migration Model Suitable for High‐Alkalinity Red Mud Filtrates and Test Verification - Bai, Bing; Wu, Haiyan; Nie, Qingke; Liu, Jingjing; Jia, Xiangxin (International journal for numerical and analytical methods in geomechanics, 2025)
ABSTRACT A theoretical model of the migration process of high‐alkalinity red mud particles in porous media was derived from granular thermodynamics, complying with the complementary motion process of two‐phase flows (i.e., hydroxide ions and red mud powder). From the perspective of energy dissipation provoked by particle migration and molecular thermal motion, a migration model of hydroxide ions and suspended particles under mixed conditions was established. This model naturally considers the complex adsorption/desorption process between hydroxide ions (or red mud particles) and a porous medium solid matrix, as well as between hydroxide ions and red mud particles. Moreover, the model reveals the dynamic process and deposition effect of suspended powder under multiphase interactions during temporal and spatial variations. The migration progression of suspended substances in the process of transient injection of red mud filtrate with different pH values and the continuous change in red mud particle injection were verified by experiments.